Jewish Revival and Respect for Islam in Nineteenth-Century Europe (American Journal of Islam and Society, 2013)
On May 17, 2013, Joseph V. Montville, director of the Esalen Institute’s “Towardthe Abrahamic Family Reunion” project (http://abrahamicfamilyreunion.org), addressed a select audience at the IIIT headquarters on pre-ZionistJewish scholarly interest in Islam.He began by recalling how German and Austro-Hungarian Jewish scholarsdiscovered remarkable similarities in the Torah, the Talmud, and theQur’an. While hardly a surprise to Muslims, this was a “major revelation andsurprise” to European Christian philologists and historians of religions. Thisnew interest emerged as Europe was losing its fear of the Ottoman Empire,and of Muslims in general, because the now militarily inferior empire was inretreat and anti-Semitism was on the rise. Jewish intellectuals sought to bluntthis latter trend by combating Christian disdain, if not hostility, of Jews andJudaism. They therefore played a major role in this scholarship, for, quotingfrom Bernard Lewis [“The State of Middle Eastern Studies,” AmericanScholar 48, no. 3 (summer 1979: 369-70)]: ...